A novel image scaling based reversible watermarking scheme for secure medical image transmission. (February 2021) - Vazhora Malayil, Manikandan; Vedhanayagam, Masilamani
Abstract: Reversible watermarking is an active research area in the field of data security. In this manuscript, a reversible watermarking scheme able for electronic patient record (EPR) transmission and medical image authentication is introduced. The proposed scheme computes an adaptive authentication code from the image to be watermarked. Further, the watermark (authentication code and EPR) are embedded into the medical image through a novel image scaling up operation. While scaling up an original image with M × M pixels by a factor of 2, 3 M 2 number of pixel intensity values in the scaled-up image needs to be approximated by considering the original pixel values. In this work, a set of rules is defined to insert authentication code and EPR data through the copying of neighborhood pixels as the missing pixel intensity values in the new scaled-up image. When the neighborhood pixels have the same intensity value, the adaptive pixel copy operation will not be successful to insert the watermark. In such cases, the bit in the least significant position uses for the watermarking process. The standard medical images downloaded OsriX dataset is used for experimental study. The results obtained show that the new scheme introduced in this manuscript surpasses the existing reversible watermarking. The scheme introduced in this paper can be used as part of an automated system where EPR data needs to be transmitted along with the medical images for better healthcare services. Highlights: Introduced a new watermarking strategy called reversible zero-watermarking scheme which integrates the characteristics of both reversible watermarking and zero-watermarking approaches. The watermarked image is obtained as a by-product of the image scaling-up operation and hence no separate procedure is required for watermarking. Proposed a secure and computationally efficient method to generate an authentication code from the original image. Proposed a tamper detection and localization process, which ensures efficient tamper detection even when the watermarked image has been affected by various signal processing operations.